The Neuroscience Behind the Stock Market's Reaction to Corporate Earnings News - Barton, Jan; Berns, Gregory S.; Brooks, Andrew M. (The Accounting Review, 2014)
ABSTRACT Using functional magnetic resonance imaging, we capture neural activity in the ventral striatum—a key area in the human brain's reward processing circuit—of 35 adult investors learning the earnings per share disclosed by 60 publicly traded companies. Before imaging, investors forecasted each company's earnings and took either a long or a short position in its stock. Consistent with prospect theory, we find strong neurobiological evidence of an asymmetric reaction to positive and negative earnings surprises. Moreover, investors' personality traits and investment positions, as well as firms' earnings predictability, modulate the brain's reaction to earnings news. We also find a strong association between the magnitude of the brain's reaction and risk-adjusted stock returns and abnormal share trading around earnings announcements for our sample firms; these findings evince the brain's reaction to earnings news as an alternative, biological measure of the information content of earnings. Data Availability: Data are available from the authors.